(untitled) (Proceedings of International Conference on Educational Discoveries and Humanities, 2024)
This article highlights the essence and characteristics of metallinguistic activity in bilingual students based on an ontolinguistic approach. Learning a foreign language differs from learning a native language, these two processes have many common features, with the sequential and simultaneous assimilation of two or more languages, different language relationships are observed, and the views of scientists on this matter are described.